Tigecycline salvage therapy for critically ill children with multidrug-resistant/extensively drug-resistant infections after surgery. (October 2018) - Song, Ying; Hu, Lei; Shu, Qiang; Ye, Jing; Liang, Jianfeng; Chen, Xi; Tan, Linhua
Highlights: Tigecycline was prescribed as for an 'off label' indication in 91% children. Clinical success was reported in 86% of the patients. No serious adverse effects of tigecycline were detected in the patients. Abstract: Objective: The aim of this study was to evaluate the efficacy and safety of salvage therapy of tigecycline in critically ill children with infections caused by multidrug-resistant (MDR)/extensively drug-resistant (XDR) bacteria after surgery. Methods: A retrospective chart review was performed of critically ill children after surgery who had received tigecycline for ≥3 days between June 2012 and May 2016 in the surgical intensive care unit of a tertiary level children's hospital. Results: Of 6442 consecutive children admitted after surgery, a total of 22 were enrolled. They had a median age of 7.5 months (interquartile range (IQR), 6 months to 4 years) and a median weight of 7.3 kg (IQR, 5.1–12.5 kg). Patients received tigecycline for a median 17 days (IQR, 12–20 days). The median intensive care unit stay was 56 days (IQR, 38–61 days) and median hospital stay was 78 days (IQR, 61–94 days). Tigecycline was prescribed as culture-directed therapy in 91% of patients and as empirical therapy in 9%. Clinical success was reported in 86% of the patients. The all-cause mortality in this cohort was 18%. No serious adverse effects of tigecycline were detected in these patients. Conclusions: Tigecycline salvage therapy was successful in 86% of critically ill pediatric patients with MDR/XDR infections after surgery, with no severe adverse effects.